The Effect of Interest Rates and Financial Performance on Stock Prices with Inflation as a Moderating Variable (Stocks Listed on the Jakarta Islamic Index Period 2014-2023) - Heru, Muhammad; Hasugian, Hotbin; Nasution, Juliana (Quantitative Economics and Management Studies, 2024)
The purpose of this study was to determine the partial and simultaneous effect of interest rate variables and financial performance on stock prices and also to determine the inflation variable moderating the effect of interest rates and financial performance on stock prices (Stocks Listed on the Jakarta Islamic Index Period 2014-2023). This research uses a quantitative approach. The population in this study were 30 JIIcompanies. The sampling technique used was purposive sampling, so as to get a sample of 10 companies. The data used is panel data. The data analysis method used in this research is multiple linear regression analysis and moderating regression analysis (MRA). The variables used in this study are Interest Rates, Earning Per Share (EPS), Debt Equity Ratio (DER), Inflation and Stock Prices. The results showed that partially interest rates and DER had no significant effect on stock prices. While EPS has a significant effect on stock prices. Simultaneously interest rates, EPS and DER have a significant effect on stock prices. In the moderation test (MRA), partially Inflation is not able to moderate interest rates, EPS and DER on stock prices. While simultaneously Inflation is able to moderate interest rates, EPS and DER on stock prices.